2019
DOI: 10.3390/nu11081837
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Type 2 Diabetes Mellitus: Prevention and Treatment

Abstract: Type 2 diabetes mellitus (T2DM) is an ensemble of metabolic diseases that has reached pandemic dimensions all over the world. The multifactorial nature of the pathology makes patient management, which includes lifelong drug therapy and lifestyle modification, extremely challenging. It is well known that T2DM is a preventable disease, therefore lowering the incidence of new T2DM cases could be a key strategy to reduce the global impact of diabetes. Currently, there is growing evidence on the efficacy of the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
173
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(184 citation statements)
references
References 74 publications
1
173
0
10
Order By: Relevance
“…Moreover, presence of IR accelerates the formation of Neuritic plaques which are involved in the pathogenic process of AD [45]. Curcumin has repeatedly demonstrated efficacy in regard to improving insulin resistance [15]. Curcumin treatment reduced both serum insulin and insulin resistance (measured via HOMA2-IR).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, presence of IR accelerates the formation of Neuritic plaques which are involved in the pathogenic process of AD [45]. Curcumin has repeatedly demonstrated efficacy in regard to improving insulin resistance [15]. Curcumin treatment reduced both serum insulin and insulin resistance (measured via HOMA2-IR).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a bio-active curcuminoid, extracted from the rhizomes of turmeric with a wide range of pharmacological properties including the ability to reduce inflammation, oxidative stress and insulin resistance [12][13][14]. In vivo studies in animal models [13] and a few clinical trials [15] have shown beneficial effects of curcumin on insulin resistance. Systematic reviews have provided strong evidence for investigating curcumin efficacy for management of type 2 diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, curcumin and extracts rich in curcumin postpone diabetes development, protect beta‐cell, decrease insulin resistance, regulate lipid metabolism, reduce diabetic cardiomyopathy, attenuate testicular injury and oxidative stress (Jin et al., 2018; Pivari, Mingione, Brasacchio, & Soldati, 2019; Rashid, Chowdhury, Ghosh, & Sil, 2017; Zha et al., 2018), as well as ameliorate diabetic complications, such as liver disorders, adipocyte dysfunction, neuropathy, nephropathy, vascular diseases, and pancreatic disorders (Zhang, Fu, Gao, & Liu, 2013). Curcumin analogs with shortened central seven‐carbon chain hardly show hypoglycemic effects but potentially helpful for alleviating diabetes complications, whereas curcumin analogs preserving this chain reserve the hypoglycemic effects.…”
Section: Mechanisms Of Dietary Polyphenols As Antidiabetic Agentsmentioning
confidence: 99%
“…The three major chemical constituents and biological activities of turmeric were approximately 77% curcumin (CUR), 17% demethoxycurcumin (DMC), and 3% bisdemethoxycurcumin (BDMC), which are belong to curcuminoids [1,2]. Cur, a linear diarylheptanoid, is a natural phenolic compound and it has been well known and used to treat many diseases, such as cancer [3][4][5][6], diabetes [7,8], inflammation [1] and neurodegenerative disorders [9,10]. In spite of the potential health benefits of CUR, its clinical applications are limited due to its low oral bioavailability, low water solubility, and instability at acidic Ph [11,12].…”
Section: Introductionmentioning
confidence: 99%